Modeling of an attendance management system performed by the pedagogical sector of the Federal University of Itajubá - Itabira Campus (Research, Society and Development, 2019)
The use of softwares has a great importance nowadays, it is possible to develop new technologies from them, to facilitate the tasks in several areas and, consequently, to bring practicality in the activities performed every day. In this situation, the article describes the modelling of a help system to the pedagogical sector of the Federal University of Itajubá - Itabira campus, with the purpose of assisting in the organization of the attendance documents created by this sector, because, currently, all the work is performed manually, which makes it difficult to process the treatments already done.  The first step was based on the client's interview, seeking to collect the informations that the client wanted to add in the software to be developed. Based on these data, the requirements were researched and categorized so that nothing important was missing in the next phases of the project. The gathered requirements were used in the next cycle, in which it was necessary to describe the functionalities of the system that will be designed, making clear to the customer how the product requested by him will work. To illustrate this step, use case diagrams have been created, presenting all external agents that will communicate with the system internally and, for each use case, an explanatory flow was created in order to show its operation. Finally, in order to organize the actions to be done during this project, the activity diagram was used and, also, the prototyping of the system interfaces was done. At the end of this article, we have the description of the necessary documentation so that the proposed system can be implemented.